The axonal chemorepellant semaphorin 3A is increased in the cerebellum in schizophrenia and may contribute to its synaptic pathology. - Eastwood, S; Law, A; Everall, I; Harrison, P (2003)
The neuropathological features of schizophrenia are suggestive of a developmentally induced impairment of synaptic connectivity. Semaphorin 3A (sema3A) might contribute to this process because it is a secreted chemorepellant which regulates axonal guidance. We have investigated sema3A in the cerebellum (an area in which expression persists in adulthood), and measured its abundance in 16 patients with schizophrenia and 16 controls. In adults, sema3A was predominantly localized to the inner part of the molecular layer neuropil, whereas infants and rats showed greater labelling of Purkinje cell bodies. Sema3A was increased in schizophrenia, as shown by enzyme-linked immunosorbent assay (+28%; P<0.05) and immunohistochemistry (+45%; P<0.01). We also measured reelin mRNA, since reelin is involved in related developmental processes and is decreased in other brain regions in schizophrenia. Reelin mRNA showed a trend reduction in the subjects with schizophrenia (-26%; P=0.07) and, notably, was negatively correlated with sema3A. Sema3A also correlated negatively with synaptophysin and complexin II mRNAs. The results show that sema3A is elevated in schizophrenia, and is associated with downregulation of genes involved in synaptic formation and maintenance. In this respect, sema3A appears to contribute to the synaptic pathology of schizophrenia, perhaps via ongoing effects of persistent sema3A elevation on synaptic plasticity. The findings are consistent with an early neurodevelopmental origin for the disorder, and the reciprocal changes in sema3A and reelin may be indicative of a pathogenic mechanism that affects the balance between trophic and inhibitory factors regulating synaptogenesis.